Identification and analysis of drought-responsive F-box genes in upland rice and involvement of OsFBX148 in ABA response and ROS accumulation - Yifan Wang; Fang Chen; Yuyang Chen; Kaiwen Ren; Dan Zhao; Kun Li; Haipeng Li; Xiaobin Wan; Mu Peng; Zhixin Xiang; Qiaoyu Tang; Zhi Hou; et al. (BMC Plant Biology)
Abstract Background Upland rice varieties exhibit significant genetic diversity and broad environmental adaptability, making them ideal candidates for identifying consistently expressed stress-responsive genes. F-box proteins typically function as part of the SKP1-CUL1-F-box protein (SCF) ubiquitin ligase complexes to precisely regulate gene expression and protein level, playing essential roles in the modulation of abiotic stress responses. Therefore, utilizing upland rice varieties for screening stress-responsive F-box genes is a highly advantageous approach. Results Through mRNA-seq analysis in the Brazilian upland rice (cv. IAPAR9), the research identified 29 drought-responsive F-box genes. Gene distribution and duplication analysis revealed these genes are distributed on 11 of the 12 chromosomes and 10 collinear gene pairs were identified on different chromosomes. 13 cis-elements or binding sites were identified in the promoters of the 29 drought-responsive F-box genes by analysis. Protein domain, stability and subcellular localization analysis results suggest that these F-box proteins possess F-box domain and several other domains, and they are mostly unstable proteins with subcellular localization in cytoplasm, nucleus, chloroplasts, mitochondria and endoplasmic reticulum. Most of drought-responsive F-box genes exhibited expression in various tissues such as root, stem, leaf, leaf sheath and panicle except for OsFBO10 and OsFBX283. These genes exhibited various responses to abiotic stresses such as osmotic, cold, heat, and salt stresses, along with ABA treatment. Importantly, a frame-shift mutation in OsFBX148 was created in the ZH11 variety, leading to altered ABA signal transduction and ROS accumulation. The study further elucidated the interaction of OsFBX148 with SKP1 family proteins OSK4/7/17 to form the SCF complex, dependent on the F-box domain. Conclusions The research identified and analyzed 29 drought-responsive F-box genes in upland rice and provides valuable insights into the role of OsFBX148 in ABA and ROS responses. It establishes a basis for future exploration of F-box genes in improving resistance to abiotic stresses, especially drought.